Destination Italy in English translation and language over the years (1919-1959) (Altre Modernità, 2025)
Destination Italy in English translation and language over the years (1919-1959)  (a cura di) Mirella Agorni  (Università Ca’ Foscari Venezia) e Ilaria Parini  (Università di Torino)  Introduction by Mirella Agorni